(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India Post is one of the largest government-backed service sector institutions with a massive customer base and a trusted reputation. India Post offers a wide range of services, including mailing services, financial services, insurance, and agency services. With its extensive network, India Post reaches remote areas where traditional banks have not yet established their presence. This allows banking services to be accessible to the masses and those who have been deprived of financial services.